2018
DOI: 10.1002/ijfe.1617
|View full text |Cite
|
Sign up to set email alerts
|

A network visualization approach and global stock market integration

Abstract: This paper applies a visualized network approach to analyse the degree of integration or comovement among global equity markets. We utilize daily prices of stock market indices of 57 countries from January 1997 to August 2012 to establish both a minimum spanning tree network and graph network. We examine network features including connectivity and centrality through a variety of indicators. Our results clearly show that there has been a tendency over time for markets to become more integrated globally even dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…These conclusions have important implications for international investors, portfolio managers and regulatory authorities. Tong et al (2018) show that the results of centrality suggest that the US and Hong Kong markets have been the most dominant markets in their geographic region. For Europe, they find 3 dominant centres, France, the United Kingdom, and Germany, in contrast to the previous literature, which suggests that the United Kingdom was the dominant country.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These conclusions have important implications for international investors, portfolio managers and regulatory authorities. Tong et al (2018) show that the results of centrality suggest that the US and Hong Kong markets have been the most dominant markets in their geographic region. For Europe, they find 3 dominant centres, France, the United Kingdom, and Germany, in contrast to the previous literature, which suggests that the United Kingdom was the dominant country.…”
Section: Introductionmentioning
confidence: 88%
“…The results of the study can be used to formulate efficient diversification strategies. Özer et al (2016), Tong et al (2018), Moagar-Poladian et al (2019) analyzed the interconnections between capital markets. Özer et al (2016) show hybrid results, failing to confirm the existence of interdependencies between the capital market of Germany, Austria, the Czech Republic, Croatia, Lithuania and Greece.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hale et al (2013) found, connections slow during global financial crises. Tong et al (2018) mapped global stock market correlations. Daily stock market index values from 57 nations were used to create these graphs and trees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The CC gauges an economy's linkages, while African countries like South Africa have fewer. Economists contend that endogenous characteristics rather than external links drive economic performance in Africa (Enisan and Olufisayo, 2009;King and Levine, 1993;Tong et al, 2018). This is because other African states are more widely scattered and geographically linked (especially to the European group).…”
Section: Equity Market Integrationmentioning
confidence: 99%
See 1 more Smart Citation